New ways to successfully target tumor vasculature in ovarian cancer - Yang, Xiaoyun (Curr Opin Obstet Gynecol, 2015)
PURPOSE OF REVIEW: The aim of this paper was to review the recent literature on potential therapeutic strategies for overcoming resistance to anti-VEGF drugs in ovarian cancer. RECENT FINDINGS: Although clinical benefits of anti-VEGF therapy were observed in ovarian cancer treatment trials, this use yielded only modest improvement in progression-free survival, and with the exception of cediranib no effect on overall survival. Adaptive resistance and escape from anti-angiogenesis therapy is likely a multifactorial process, including induction of hypoxia, vascular modulators and the immune response. New drugs targeting the tumor vasculature or other components of the surrounding microenvironment have shown promising results. SUMMARY: When to start and end antiangiogenesis therapy and the choice of optimal treatment combinations remain controversial. Further evaluation of personalized novel angiogenesis-based therapy is warranted. Defining the critical interaction of these agents and pathways and the appropriate predictive markers will become an increasingly important objective for effective treatment.